"I HEAR MY VOICE, BUT WHO IS TALKING?": UNDERSTANDING DEPERSONALIZATION. (October 2015) - HAFT, JACQUELINE
<x xml:space="preserve">Abstract</x> Depersonalization is the frightening experience of being a shut‐inside, ghostlike, "true" self that observes another part of the self interacting in the outside world. The "true" self hides safely within, while the "participating" self holds all affects and impulses. This split in the ego is created via internal projective identification in the face of overwhelming affect, unavailability of adequate identifications, and insufficient support for psychic cohesion. As the transference develops, the powerful entrapping cocoon of depersonalization can be projected onto the now‐entrapping analyst, where it can be addressed. A clinical vignette illustrates these points.